2022
DOI: 10.3390/cells11050769
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-139, an Emerging Gate-Keeper in Various Types of Cancer

Abstract: Mounting data show that MIR139 is commonly silenced in solid cancer and hematological malignancies. MIR139 acts as a critical tumor suppressor by tuning the cellular response to different types of stress, including DNA damage, and by repressing oncogenic signaling pathways. Recently, novel insights into the mechanism of MIR139 silencing in tumor cells have been described. These include epigenetic silencing, inhibition of POL-II transcriptional activity on gene regulatory elements, enhanced expression of compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 126 publications
(185 reference statements)
0
5
0
Order By: Relevance
“…In this group, miRNA-150 and miR-139 were significantly elevated compared to non-drinkers ( Figure 3 ). MiR-150 is suggested to play a protective role in the heart [ 84 ], while MiR-139 is discussed as gate-keeper in cancer while acting against different types of stress, including DNA damage [ 85 ]. This may indicate a specific regulatory pathway through which moderate alcohol consumption exerts its protective effects on heart health.…”
Section: Discussionmentioning
confidence: 99%
“…In this group, miRNA-150 and miR-139 were significantly elevated compared to non-drinkers ( Figure 3 ). MiR-150 is suggested to play a protective role in the heart [ 84 ], while MiR-139 is discussed as gate-keeper in cancer while acting against different types of stress, including DNA damage [ 85 ]. This may indicate a specific regulatory pathway through which moderate alcohol consumption exerts its protective effects on heart health.…”
Section: Discussionmentioning
confidence: 99%
“…[66][67][68] It is worth mentioning that, by contrast to ACC, miR-139-5p is underexpressed in AML, GC and CRC and acts as a tumour-suppressor miRNA in many cancers. 69,70 To strengthen our observations in vitro, we analyzed the relationship between Wnt/β-Catenin pathway mutational status and miR-139-5p levels in ACC patients. Importantly, we found that patients with mutations have significantly higher levels of PDE2A and miR-139-5p and a significantly lower level of NDRG4 when compared to patients with no known mutation in the Wnt/β-Catenin pathway.…”
Section: Discussionmentioning
confidence: 99%
“…66-68 It is worth mentioning that, by contrast to ACC, miR-139-5p is underexpressed in AML, GC and CRC and acts as a tumour-suppressor miRNA in many cancers. 69, 70…”
Section: Discussionmentioning
confidence: 99%
“…Numerous reports of altered miRNA expression have been linked to various pathologies [ 11 , 12 , 13 ], including BC [ 14 , 15 ]. MiRNAs are small non-coding RNAs that regulate gene expression in key biological processes such as proliferation, apoptosis, invasion, and metastasis [ 16 , 17 , 18 ] and have recently emerged as regulators of the complex mechanisms that drive BC therapeutic resistance or sensitivity. Extracellular vesicles (EVs) are small lipid bilayer-encapsulated vesicles that are released by living cells in the microenvironment.…”
Section: Introductionmentioning
confidence: 99%